PERANCANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF DENGAN MENGGUNAKAN APLIKASI FLASH - Zurnawita zurnawita (Teknik Elektro Politeknik Negeri Padang, 2013)
The rapid development of multimedia technology can be utilized by the world of education, particularly in improving the way of learning to the learning process can be developed and not left behind by technological advances. In this research the development of multimedia applications in education. This application provides an interactive material with animation, audio, video and comes with an evaluation form about the exercises. Results will be achieved of the media making this learning is that students can understand subjects of digital system. It is expected that these applications can facilitate the learning process improve the quality of teaching and learning achievement